THERAPEUTIC POTENTIAL OF SNAIL MUCUS IN WOUND HEALING : A SYSTEMATIC REVIEW AND META-ANALYSIS - Widjaja, Febe Alodia; Saputro, Iswinarno Doso; Asmaradianti, Aryunidya; Sindhu, Florencia Christina; Fabian, Pascalis; Irsyan Baginda Maulana (Jurnal Rekonstruksi dan Estetik, 2025)
Highlights: Snail mucus extract significantly improves wound healing rates compared to standard treatments. A meta-analysis of randomized controlled trials (RCTs) showed a statistically significant effect (MD = -3.21%, P < 0.00001). The bioactive compounds in snail mucus promote collagen production and reduce inflammation. Abstract Introduction: Wound healing is a fundamental biological process comprising four sequential and overlapping phases: hemostasis, inflammation, proliferation, and remodeling. The successful restoration of tissue integrity requires that these phases proceed in the correct order and within an appropriate temporal framework. Proteins are indispensable to this process, as they mediate tissue growth, cellular renewal, and reparative mechanisms. Snail mucins, a class of large glycosylated proteins, have been reported to facilitate wound healing by stabilizing protein structures, modulating solubility and viscosity, and enhancing cell–cell recognition. In light of these properties, we conducted a meta-analysis of randomized controlled trials (RCTs) to assess the therapeutic efficacy of snail mucus extract in promoting wound repair. Method: RCTs on snail mucus extract for wound healing were identified through searches of PubMed, ProQuest, Web of Science, ScienceDirect, Scopus, EBSCOHost, and ClinicalTrials.gov. The review adhered to PRISMA guidelines, applied the PICO framework, and assessed study quality using the JADAD scale. Result: A total of 60 rats from three RCTs conducted between 2021 and 2023 were included in the meta-analysis. The findings demonstrated that the snail mucus group exhibited a significantly improved wound healing rate compared to the control group (MD = -3.21%, 95% CI: -3.72 to -2.69%, P < 0.00001). Conclusion: Snail mucus extract has been shown to significantly accelerate wound healing in animal models; however, further clinical studies are required to confirm its therapeutic efficacy in humans.